GAMBARAN PERILAKU MEROKOK SISWA MTS DI PURWAKARTA - Aeni Desi Fitria Malik; Siti Fatimah; Tuti Alawiyah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
The purpose of this study was to identify the number of smokers and the description of the causes of smoking behavior in adolescent students, especially class VIII MTs. This research used qualitative descriptive method involving 6 students as research samples taken from 30 students of class VIII. Data collection techniques and sample selection through the distribution of questionnaires. Based on the resulted of the research related to the description of smoking behavior in class VIII MTs in Purwarkarta, from total 30 students. the researcher can draw the conclusion that it was found that a total of 6 students (20%) smoke and 24 students (80%) did not smoke. The students who have a level of addiction to cigarettes are categorized from the number of smokers, 4 students (66%) are heavy smokers and 2 students (34%) are moderate smokers. Factors behind this include peers, curiosity, the community and family who smoke. Keywords: : Smoking behavior, MTs Students